Product Selection of Face Masks for Sensitive Skin Using the Composite Performance Index (CPI) Method - Nugroho, Prasetiyanto; Azhari, Ahmad (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
The more face mask products for sensitive facial skin that are created, consumers also feel confused by several considerations such as excessive side effects for the mask products they will use so as not to worsen the condition of the facial skin. Therefore, to help consumers in choosing the right face mask in terms of consideration of benefits, side effects that will be caused, and affordable prices, the authors compiled a study with the title